Strategi Komunikasi Agama dan Budaya (Studi Dakwah Jamaah Tabligh di Kebon Jeruk Dki Jakarta) - Hafniati, Hafniati (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This research aims to analyze the religious and cultural communication strategies used by the Tablighi Jamaah in their da'wah activities in Kebon Jeruk, DKI Jakarta. Using a case study approach, using descriptive qualitative methods. This research explores how the Tablighi Jamaah adapts religious messages to cultural contexts, as well as the communication methods they employ to reach the community. The research results show that the Tablighi Jamaah succeeded in building effective communication through an informal approach, emphasis on religious practices, use of simple language, and providing real role models. Intelligent cultural adaptation and a deep understanding of the social context of the Kebon Jeruk community are key factors in the success of their da'wah. This research provides insight into the importance of contextual communication strategies in religious propagation, as well as their relevance in a multicultural society such as DKI Jakarta.